Comprehensive investigation and quantification of quality repeatability for laser powder bed fusion processed 316L stainless steel - Huang, De Jun (Nanyang Technological University, 2022)
Laser Powder Bed Fusion (L-PBF) additive manufacturing has gained traction in several industries as a result of the recent progress in machine and material development. However, the repeatability of part quality remains as a bottleneck for large-scale implementations of this technology to make economic sense in the industry. This research aims to effectively investigate and quantify quality repeatability in L-PBF process in order to drive better adoption and make repeatability studies more accessible in the future. Three major studies were conducted to identify, understand and track the important L-PBF parameters beyond the classical ones to the process repeatability.